Fraudulent consumers: The attitudes of young people to consumer-initiated fraud against business - Leyland Pitt (South African Journal of Business Management, 1982)
One of the most perturbing facts about deviant consumer behaviour is that the vast majority of fraudulent acts are committed by young people. Researchers are of the opinion that deviant consumer behaviour is essentially a question of attitudes. The study described in this article parallels one conducted by Wilkes in the USA, differing in that the research was carried out on young respondents. The objectives were to determine: attitudes towards fraudulent consumer activities; whether differences exist between the attitudes of male and female respondents; whether the results would differ significantly from the Wilkes study; and attitudes towards a further five situations not used in the Wilkes study. The results obtained amplify Wilkes' findings in every way. The article concludes that business should take a close look at its own approach to security, and that fraudulent consumer behaviour is the result of attitudes such as 'they can afford it' and 'it's not really stealing'.